Injured Cyclists’ Experiences of Risk Factors: A Content Analysis - Naema Khodadadi-Hassankiadeh; Farshad Sedaghati Voshme Saraei; Leila Kouchakinejad‑Eramsadati; Fateme Keihanian; Marieh Hosseinpour (Bulletin of Emergency and Trauma)
Objective: Cycling is a healthy and pleasurable activity, but it can also be hazardous. The risk factors for cycling injury are unknown, considering the cycling infrastructure and cyclists’ behavior in northern Iran. This study aimed to explain the experiences of injured cyclists admitted to Poursina Educational and Medical Center, Rasht in 2021, as one of the risk factors associated with cycling.Methods: A content analysis was conducted on the experiences of cyclists over the age of 18 who had one or more injured limbs due to a crash or fall while riding a bicycle. The data were obtained from the registration system of the Guilan Road Trauma Research Center. Potentially eligible participants were contacted by telephone. Twenty people with various characteristics in terms of age, sex, and other features were included in the interview. Results: Cyclists’ experiences with risk factors were divided into 13 categories; including lack of laws, lack of training, poor traffic culture, easy to lose balance, cycling infrastructure, inappropriate roads, darkness, bad weather conditions, unsafe behavior, non-standard bicycle, unsafe protection, intentional injury to female road users, and risk of collision with other road users.Conclusion: The extracted risk factors can be used as the ABC of cycling to novice cyclists. Thus, responsible efforts to regulate, educate, promote, and monitor cycling can encourage people to ride.